Improving the efficiency of the screw unit of plastering plants - Salnikov, Roman; Rudyk, Rostyslav (Academic journal Industrial Machine Building Civil Engineering, 2023)
The article focuses on enhancing the efficiency of screw units in small-sized plastering installations for pumping mortars within the construction industry. It delves into the analysis of existing plastering unit structures, evaluating their respective advantages and disadvantages. Additionally, the article provides an overview of various mortar pumps and their associated parameters. A key objective of the study is to conduct a comparative analysis of current small-sized plastering unit designs and to elevate the effectiveness of mortar pumping. Mathematical models are presented to determine coefficients that consider the non-uniformity of conditions for the concrete mixture's end, as well as the necessary pressure for optimal filling of the working cylinder with the concrete mixture. Furthermore, the article explores the utilization of innovative technologies and materials to enhance the efficiency and functionality of the screw unit.